Mortalidade hospitalar por síndrome respiratória aguda grave pela covid-19 no interior e região metropolitana do Brasil, 2020-2021 - ARAÚJO, Mayra Sharlenne Moraes (2023)
Introduction: Mortality data helps us understand the severity of a disease, identify the most affected populations and reflect on the quality of care provided. The COVID-19 pandemic has a high mortality rate for the entire population in Brazil and worldwide. The population can be affected in different ways based on age, gender, social characteristics and geographical location. Brazil has a vast territorial extension and can be divided according to its regions, states and even metropolitan and interior regions. Objective: To analyze the hospital mortality rate for Severe Acute Respiratory Syndrome due to COVID-19 in the interior and metropolitan regions of Brazil in 2020 and 2021. Method: Ecological study of cases and deaths from Severe Acute Respiratory Syndrome due to COVID-19 recorded in Brazil. The study population consisted of all cases registered in 2020 and 2021 in the Influenza Epidemiological Surveillance Information System, available in the OpenDATASUS database. Clinical, epidemiological and demographic variables were used, as well as the evolution and final classification of the Individual Case Record Sheet for Severe Acute Respiratory Syndrome due to COVID-19. This thesis was divided into two articles. In the first article, the age range used was 0 to 80 and over, while in the second article the age range was 0 to 19. As a demographic classification, the division of Brazil available from the Brazilian Institute of Geography and Statistics (IBGE) was used as metropolitan region and interior. The data was analyzed using the open access software R version 4.0.4. Pearson's chi-square test was used to assess differences between demographic, clinical and epidemiological characteristics between groups, considering a significance level of 5%. Results: In the first study, there were 1,777,232 cases and 603,339 deaths, 68% of which occurred in people aged 60 or over. In the interior and the metropolitan region, in 2021, there was an increase in the Hospital Mortality Rate (HMR) among people aged 20-79 and a reduction in those aged 0-19 and 80 and over. In the second study, in the Metropolitan Region and the Interior, the highest HMR were seen among those who used invasive ventilatory support, reaching 61.29% in 2020 in the 0-28 day group in the Interior and 54% in the 15-19 year old group in the Metropolitan Region. In 2021, several HMRs decreased, but still maintained exponential values. Conclusion: It was expected that the HMR would improve in 2021, but in some groups it remained the same and in others it increased. The child and adolescent population had lower HMRs than the general population. It is assumed that mortality from COVID-19 is higher than that seen in this study, considering problems of under-reporting and under-registration.